SIOP PODC Adapted treatment guidelines for low grade gliomas in low and middle income settings. (3rd January 2018) - Hessissen, Laila; Parkes, Jeannette; Amayiri, Nisreen; Mushtaq, Naureen; Sirachainan, Nongnuch; Anacak, Yavuz; Mitra, Dipayan; Figaji, Anthony; Schouten‐van Meeteren, Antoinette; Sullivan, Michael; Burger, Hester; Davidson, Alan; et al.
Abstract: Effective treatment of children with low grade glioma (LGG) requires a functioning multi‐disciplinary team with adequate neurosurgical, neuroradiological, pathological, radiotherapy and chemotherapy facilities and personnel. In addition, the treating centre should have the capacity to manage a variety of LGG and treatment‐associated complications. These requirements have made it difficult for many centers in low and middle‐income countries (LMIC) to offer effective treatment and follow up. This article provides management recommendations for children with LGG according to the level of facilities available.